Les choix d’investissements publics en culture et le développement durable : sous quelles conditions ? - Virginie Proulx (VertigO)
For as long as we can remember, arts and culture have thrived in societies. Sometimes by leaving them a great heritage, sometimes by amusing people, other times, more recently, by attracting tourism, by providing a city brand and sometimes, by educating and cultivating people. For the leaders of yesterday and today, from here and there who have invested in culture, the story has shown that this is what allows societies to grow, to develop their creativity, to be recognized and share their knowledge. We realize more and more concretely how culture contributes to the development of large cities : Barcelona and Paris have made it their strength. But can we presume that culture could also be a vector of development for small regional cities ? And if so, what are the different ways to invest in culture so that it contributes to development in a sustainable way ? How can public decisions toward different forms of culture and various processes involved in its development (infrastructures, artistic production, distribution, marketing, promotion of cultural tourism) influence impacts on sustainable territorial development today ? Our study is based on an analysis of local actors speech in Rimouski about public investments in culture and sustainable development.